Urgensi Kualitas SDM, Budaya Organisasi, Knowledge Sharing, dan Teknologi Terhadap Terciptanya Learning Organization - Gunawan Aji; Dian Alvianita; Wulan Suryaningsih; Hayu Naila Nadzifa; Nabilatul ‘Athifah (Lembaga Pengembangan Kinerja Dosen, 2023)
Along with the times, the establishment of the company will be more difficult to maintain its existence. This is influenced by the existence of intense business competition. From this reality, if a company does not have the ability to develop itself, it cannot be denied that there is a possibility of business setbacks. As for one form of effort that can be applied by companies to improve their competence or performance in order to survive in the business competition that occurs and encouragement to have the ability to adapt to the business environment is in the form of implementing the concept of learning organization in which this concept can support the goal of maintaining the company's survival as expected. business actors and employees. The method used in this study is literature review with a qualitative approach using analytical techniques in the form of descriptive analysis. As for the research that has been done, the results show that there is a high level of urgency from the variables of HR Quality, Organizational Culture, Knowledge Sharing, and Technology for the Creation of a Learning Organization.